PENGARUH BIAYA PRODUKSI DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH: (Perusahaan Consumer Goods Yang Terdaftar di Bursa Efek Indonesia Periode 2016 - 2020) - robi maulana (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
This study aims to determine the effect of production costs and operating costs on net income. This type of research is descriptive and verification research using a quantitative approach. The population in this study are consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 – 2020. The sampling technique uses purposive sampling, the samples used in this study amounted to 11 companies with a 5 year period of observation to 55 sample data. The data used in this research is secondary data. The data analysis method in this study is descriptive, classical assumption test, multiple linear, coefficient of determination, model feasibility test and hypothesis testing with SPSS version 25 software tools. The results showed that production costs affect net income, meaning that the higher the production costs, the higher the company's net profit. And operating costs have an effect on net income, meaning that the higher the operational costs, the higher the company's net profit